Dominating deformation mechanisms in ultrafine-grained chromium across length scales and temperatures. (November 2017) - Fritz, R.; Wimler, D.; Leitner, A.; Maier-Kiener, V.; Kiener, D.
Abstract: The microstructure influence on the thermally activated deformation behaviour of chromium is investigated for a more fundamental understanding of the deformation mechanisms contributing to plasticity in bcc metals. Therefore, scale-bridging experiments at variable temperatures and varying strain-rates are performed, encompassing macroscopic compression tests in direct correlation to local in-situ SEM micro-compression experiments on taper-free pillars and advanced nanoindentation testing. For the first time, it is demonstrated that, independent of stress state, sample volume and surface fraction, a distinct temperature-dependent transition of the dominating deformation mechanism occurs. While at low temperatures the lattice resistance dominates, exceeding a critical temperature the dislocation interaction with grain boundaries becomes the rate limiting step. Finally, based on the vastly different fractions of grain boundaries in the tested sample volumes, a comprehensive model on the deformation of bcc metals, in particular at small scales or for confined volumes is derived. Graphical abstract: Image 1